Surface acidity enhancement of CeO2 catalysts via modification with a heteropoly acid for the selective catalytic reduction of NO with ammonia. Issue 20 (30th September 2019) - Ke, Yu; Huang, Wenjun; Li, Sichao; Liao, Yong; Li, Jiaxing; Qu, Zan; Yan, Naiqiang
Abstract : The surface acidity enhanced CeO2 catalysts exhibited a SCR reaction path that both mechanisms existed but E-R dominated. Abstract : Vanadium-free catalysts for ammonia selective catalytic reduction (NH3 -SCR), such as CeO2 -based catalysts, often have low activities over a wide reaction window, and low N2 selectivity. These limitations can be overcome by increasing the surface acidity of the catalyst and adjusting its surface defects and vacancies. In this study, a series of silicotungstic acid (HSiW)-modified CeO2 samples was prepared, and their NH3 -SCR performances were evaluated. The experimental results indicated that 10% HSiW/Ce achieved a NO conversion of over 90% in the temperature region of 226–400 °C with 99% N2 selectivity. The HSiW was well-dispersed over the surface of CeO2 and maintained its Keggin-type structure, leading to an increase in Brønsted acid sites in the catalyst. The adsorption of NH3 during the SCR reaction was greatly improved, resulting in higher activity. In addition, the incorporation of HSiW changed the redox properties of CeO2 by decreasing the concentration of Ce 3+ and vacancies. During the reaction process, the peroxidation of NH3 at high temperature was inhibited due to the decreased surface-adsorbed oxygen and Ce 3+, leading to improved N2 selectivity. The reaction mechanism was also studied using in situ diffuse reflectance infrared Fourier transform (DRIFT) experiments. Although both the L–H and E–R mechanisms could occur during the SCR reaction, the E–R mechanism may dominate under the experimental conditions. Overall, modification with HSiW is a satisfactory method to improve the SCR activity of CeO2 .